Intelligent Decision Technologies 2018 Proceedings of the 10th KES International Conference on Intelligent Decision Technologies (KES-IDT 2018) - Czarnowski, Ireneusz; Howlett, Robert J.; Jain, Lakhmi C.; Vlacic, Ljubo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book gathers the proceedings of the KES-IDT-2018 conference, held in Gold Coast, Queensland, Australia, on June 20-22, 2018. The conference provided opportunities to present and discuss the latest research results, promoting knowledge transfer and the generation of new ideas in the field of intelligent decision-making. The range of topics explored is wide, and includes methods for decision-making, decision support, data analysis, modeling and many more in areas such as finance, economics, management, engineering and transportation. The book contains several sections devoted to specific topics, such as: · Decision-Making Theory for Economics · Advances in Knowledge-based Statistical Data Analysis · On Knowledge-Based Digital Ecosystems & Technologies for Smart and Intelligent Decision Support Systems · Soft Computing Models in Industrial and Management Engineering · Computational Media Computing and its Applications · Intelligent Decision-Making Technologies · Digital Architectures and Decision Management.
Designing Interactive Topic Discovery Systems for Research and Decision Making -- Multivariate Multiple Orthogonal Linear Regression -- An Application of Transfer Learning for Maritime Vision Processing using Machine Learning -- Decision-oriented Composition Architecture for Digital Transformation -- Non-reciprocal Pairwise Comparisons and Solution Method in AHP -- A Questionnaire Method of Class Evaluations Using AHP with a Ternary Graph -- Measurement of Line-of-Sight Detection Using Pixel Quantity Variation for Autistic Disorder -- Irradiation of the Ear with Light of LED for Self- Awakening -- Projection Mapping of Animation by Object Recognition -- Development of Recovery of Eye-fatigue by VDT Works.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence